2011
DOI: 10.1042/bj20101810
|View full text |Cite
|
Sign up to set email alerts
|

When a module is not a domain: the case of the REJ module and the redefinition of the architecture of polycystin-1

Abstract: Synopsis The extracellular region of a group of cell surface receptors known as the polycystic kidney disease 1 family, comprising amongst others polycystin-1, has been controversially described as containing four fibronectin type III (FNIII) domains or one REJ module in the same portion of polypeptide. Stimulated by recent atomic force microscopy work we re-examined the similarity of these four domains with a FNIII sequence profile showing the evolutionary relationship. Two of the predicted domains could be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…This is in agreement with a recent study that found that REJd1, -d2, -d3, and -d4 are very hard to express in E. coli [24]. In order to increase their solubility we flanked the REJ domains with maltose-binding protein (MBP) and titin I27 domains.…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…This is in agreement with a recent study that found that REJd1, -d2, -d3, and -d4 are very hard to express in E. coli [24]. In order to increase their solubility we flanked the REJ domains with maltose-binding protein (MBP) and titin I27 domains.…”
Section: Methodssupporting
confidence: 87%
“…1 from PC1 (1b4r) and the human PKD domain from protein KIAA0319 (2e7m). The domain boundaries were based on Schröder et al sequence analysis [24] and our Clustal multiple sequence alignment. The overall identity between each of the REJ domains and the template structures was low (~10% overall identity, ~27% similarity).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 65% and 75% of pathogenic mutations in PKD1 are either nonsense, splice site, or insertion/deletion changes that are predicted to result in premature termination of the PC1 pep like PKD repeats (34)(35)(36), a receptor egg jelly (REJ) domain (37) that includes fibronectin type III repeats (38) and is part of a recently identified structural GAIN domain (39). The REJ/GAIN domain is required for autoproteolytic cleavage of PC1 at a G protein-cou pled receptor proteolytic site (GPS) sequence, HL↓T 3049 (40), that yields an extracellular NH 2 terminal fragment (PC1-NTF) and an intramembranous COOHterminal fragment (PC1-CTF) (39,41,42).…”
Section: L3040hmentioning
confidence: 99%
“…1D NMR spectra were recorded on a 700 MHz Bruker Avance spectrometer using watergate for water suppression [59] as described previously [60]. Diffusion coefficients were measured on a Bruker Avance 500 MHz spectrometer using a convection compensated double stimulated echo experiment [61].…”
Section: Methodsmentioning
confidence: 99%